Single-cell sequencing revealed metabolic reprogramming and its transcription factor regulatory network in prostate cancer - Wei, Guojiang; Zhu, Hongcai; Zhou, Yupeng; Pan, Yang; Yi, Bocun; Bai, Yangkai (Translational oncology, 2024)
•Unveiling Metabolic Reprogramming in Prostate Cancer and the Significance of SREBPs: Insights from Single-Cell Sequencing.•Unlocking Metabolic Variations and Transcription Factor Dynamics Across Distinct Prostate Cancer Subtypes via Single-Cell Sequencing.•The SREBP Inhibitor Betulin Elicits Remarkable Efficacy in Prostate Cancer Suppression. Prostate cancer is the most frequently diagnosed cancer among men in the United States and is the second leading cause of cancer-related deaths in men. The incidence of prostate cancer is gradually rising due to factors such as aging demographics and changes in dietary habits. The objective of this study is to investigate the metabolic reprogramming changes occurring in prostate cancer and identify potential therapeutic targets. In this study, we utilized single-cell sequencing to comprehensively characterize the alterations in metabolism and the regulatory role of transcription factors in various subtypes of prostate cancer. In comparison to benign prostate tissue, prostate cancer displayed substantial metabolic variations, notably exhibiting heightened activity in fatty acid metabolism and cholesterol metabolism. This metabolic reprogramming not only influenced cellular energy utilization but also potentially impacted the activity of the androgen receptor (AR) pathway through the synthesis of endogenous steroid hormones. Through our analysis of transcription factor activity, we identified the crucial role of SREBPs, which are transcription factors associated with lipid metabolism, in prostate cancer. Encouragingly, the inhibitor Betulin effectively suppresses prostate cancer growth, highlighting its potential as a therapeutic agent for prostate cancer treatment. [Display omitted]